MANIFESTATIONS OF PSYCHOLOGICAL DEFENSES OF CREATIVE PERSONALITY OF TECHNICAL SPECIALIZATION STUDENTS - Проскурка, Н.; Синчук, В.; Бойченко, М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article describes the problem of effective use of psychological defense mechanisms as a method of solving intrapersonal conflicts of creative personalities of technical specialization students. An analysis of theoretical approaches to understanding the concept of psychological defense mechanisms and their role in the structure of personality is presented. Much attention is given to the comparison of the interpretation of the functions of defense mechanisms in terms of humanistic and psychoanalytic approaches. The dynamics of the development of psychological mechanisms is considered, which, in terms of the creatological approach, is based on three stages: the existence of defense mechanisms; transition from defensive to socialization mechanisms; transformation in the mechanisms of creativity. Furthermore, the article describes the positive aspects and methods of using defense mechanisms for eliminating frustration situations by creative personalities by understanding, structuring and dynamizing unconscious components of the system of psychological defenses. The article describes the results of empirical research of the level of personal creativity and creative thinking of technical specialization students, it included primary diagnosis of the level of personal creativity O. Tunick and diagnosis of creative thinking E. Torrances (modification A. Voronin) respectively, after which a secondary diagnosis of the defense mechanisms of students with a high level of creativity was organized and based on the method of Plutchik-Kellerman-Conte. It is concluded that there is a presence in technical specialization students with a high level of creativity of a certain combination of dominant psychological defense mechanisms, such as: denial, compensation, displacement and intellectualization. The article presents the analysis of individual defense mechanisms (denial, compensation, displacement and intellectualization) of technical specialization creative students from the point of view of psychological substantiation of their effectiveness and conclusion of the prevailing constructive nature of the mechanisms was made